A microspectroscopic insight into the resistivity switching of individual Ag–TCNQ nanocrystals1. Issue 28 (28th July 2015) - Rösner, Benedikt; Ran, Ke; Butz, Benjamin; Schmidt, Ute; Spiecker, Erdmann; Fink, Rainer H.
<x xml:space="preserve">Abstract</x> We investigate the resistivity switching in individual Ag–TCNQ wires with on/off-ratios of up to 103.